Will improving access to dental care improve oral health‐related quality of life?. (5th May 2013) - Crocombe, LA; Mahoney, GD; Spencer, AJ; Waller, M
Abstract Background The aim of this study was to determine if Australian Defence Force (ADF) members had better oral health‐related quality of life (OHRQoL) than the general Australian population and whether the difference was due to better access to dental care. Methods The OHRQoL, as measured by OHIP‐14 summary indicators, of participants from the Defence Deployed Solomon Islands (SI) Health Study and the National Survey of Adult Oral Health 2004–06 (NSAOH) were compared. The SI sample was age/gender status‐adjusted to match that of the NSAOH sample which was age/gender/regional location weighted to that of the Australian population. Results NSAOH respondents with good access to dental care had lower OHIP‐14 summary measures [frequency of impacts 8.5% (95% CI = 5.4, 11.6), extent mean = 0.16 (0.11, 0.22), severity mean = 5.0 (4.4, 5.6)] than the total NSAOH sample [frequency 18.6 (16.6, 20.7); extent 0.52 (0.44, 0.59); severity 7.6 (7.1, 8.1)]. The NSAOH respondents with both good access to dental care and self‐reported good general health did not have as low OHIP‐14 summary scores as in the SI sample [frequency 2.6 (1.2, 5.4), extent 0.05 (0.01, 0.10); severity 2.6 (1.9, 3.4)]. Conclusions ADF members had better OHRQoL than the general Australian population, even those with good access to dental care and self‐reported good general health.